A new species of fish parasitic isopod, Lobothorax bharat sp. nov. (Isopoda: Cymothoidae) from Trichiurus lepturus Linnaeus 1758 (Scombriformes: Trichiuridae), India - Mohapatra, Sandeep Kumar; Roy, Sanmitra; Seth, Jaya Kishor; Tripathy, Basudev; Mohapatra, Anil (Zootaxa, 2025)
Lobothorax bharat sp. nov., is described based on specimens collected in 2023 from Trichiurus lepturus Linnaeus, 1758, at the Bahabalpur and Gopalpur fish landing centres of Odisha coast, India. Lobothorax bharat sp. nov. can be identified by the sub-truncate rostrum; the anterolateral processes of pereonite 1 which are 0.45 times the cephalon length, do not extend beyond the anterior margin of cephalon; a distinct depression in the middle of pereonite 1; article 3 of maxilliped palp with three recurved robust setae; the pereopod 2 is larger than the first and the pereopod 3 being the smallest; the third pereopod is about 0.94 times that of the second and 0.97 times that of the first pereopod. Lobothorax bharat sp. nov. is further differentiated from the congeneric species L. typus in the nucleotide composition of the mitochondrial cytochrome c oxidase I (mtCOI) gene by 2.5–2.6% Kimura-2-Parameter (K2P) distance (having a base pair difference of 16–17) and belongs to a separate cluster in the Maximum Likelihood tree analysis obtained through the best-fit model.